Pengembangan Bahan Ajar Membaca Teks Deskripsi untuk Siswa Kelas VII SMP/MTs - Arshal Zairuby Harahap; Abdul Razak; Charlina Charlina (Universitas Majalengka, 2021)
Bahan ajar merupakan salah satu faktor keberhasilan guru dalam mengajar. Bahan ajar disusun untuk membantu guru dan siswa dalam kegiatan pembelajaran. Namun, penyediaan materi dalam bahan ajar di sekolah khususnya SMP kelas VII masih minim. Guru cenderung menggunakan bahan ajar seadanya, sehingga berdampak pada rendahnya hasil belajar siswa. Dalam hal ini perlu adanya penelitian tentang pengembangan bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs. Fokus penelitian ini ialah: 1) bagaimanakah prosedur pengembangan bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs, 2) bagaimanakah profil bahan membaca teks deskripsi untuk siswa kelas VII SMP/MTs. Selaras dengan itu, tujuan penelitian pengembangan ini ialah mendeskripsikan prosedur pengembangan bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs dan mendeskripsikan profil bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs. Model pengembangan yang digunakan ialah model ADDIE, yang meliputi analysis (analisis), design (merancang), development (mengembangkan), implementation (menguji cobakan), dan evaluation (merevisi). Data dalam penelitian pengembangan ini tergolong data kualitatif, yang meliputi: 1) data validasi tahap analisis keperluan tentang KD dan indikator pencapaian kompetensi, 2) data validasi tahap analisis keperluan, 3) data validasi tahap rancangan produk, 4) data validasi tahap pengembangan produk, dan 5) data validasi kelayakan bahan ajar membaca teks deskripsi. Hasilnya, prosedur pengembangan bahan ajar model ADDIE menghadirkan sebuah produk bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs. Kemudian, profil produk bahan ajar membaca teks deskripsi untuk siswa kelas VII SMP/MTs diberi judul Inilah Tamanku.Kata kunci: penelitian pengembangan, bahan ajar, membaca, teks deskripsi Teaching materials are one of the success factors of teachers in teaching. Teaching material are prepared to assist teachers and students in learning activities. However, the provision of materials in teaching materials in the school, especially junior high school grade VII is still minimal. Teachers tend to use basic teaching materials, thus impacting on the low learning outcomes of students. In this case, there needs to be research on the development of teaching materials to read description text for grade VII SMP/MTs students. The focus of this research is: 1) what is the procedure for developing teaching materials to read descriptive text descriptions for grade VII SMP/MTs students, 2) how is the profile of teaching materials to read descriptive text for grade VII SMP/MTs. In line with that, the purpose of this development research is to describe the procedure of developing teaching materials to read the description text for grade VII SMP/MTs students and describe the profile of teaching materials to read the description text for grade VII SMP/MTs students. The development model used is the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The data in this development research is classified as qualitative data, which includes: 1) validation data of the analysis stage of the need about KD and competency achievment indicators, 2) validation data of the analysis stage, 3) validation data of the product design stage, 4) validation data of the product development stage, and 5) validation data of the feasibility of teaching materials reading the description text. As a result, the procedure for developing ADDIE model teaching materials presents a product of teaching materials to read the description text for grade VII SMP/MTs students. Then, the product profile of teaching materials for reading descriptive text for seventh grade students of SMP/MTs is entitled This is My Garden.Keywords: research development, teaching materials, reading, description text